História da paisagem do Conjunto dos Contos, Ouro Preto, MG (1750-2023) - Raíssa de Keller e Costa (2023)
This thesis is a study of the set composed of the Largo, Chafariz, Ponte, and Casa dos Contos, which we call Conjunto dos Contos (CDC), located in Ouro Preto (OP), Minas Gerais, in the period between 1750 and 2023. The city is protected in its entirety and is also the stage of countless conflicts and disputes that are not always put in evidence. Its attributes give it historical and cultural notoriety internationally, as it has been on the UNESCO World Heritage list since 1980, a city alive. We adopt the notion of landscape as a reading of space and understand that it is based on the experience and perception of those who live it, experience it, understanding that the relationship of the body with the space is primordial, as interrelated and inseparable elements. Besides having become an object of the preservation institutions' policies, landscape is also a way of thinking. In the urban perimeter of OP, the CDC is a space of intense collective use with functions that vary throughout its history and essential to the functioning of the city. The Largo surrounds and gives access to the Bridge, the Fountain, and the Casa dos Contos, all of which are classified as monuments and are today in a good state of conservation. The study of the history of the CDC starts from the dynamics of these monuments, bringing clues about daily uses, values, conflicts, diversity, and importance to the city. Moreover, this history allows us to understand the relations between public and private and the successive transformations in urban space that also brought new dynamics and conflicts. The thesis performs a reading of the history of the landscape that highlights its socio-technical context from textual and imagetic documents. The sources of the past were surveyed in archives and libraries; those of the present were produced in the form of notes in our notebook and visual records, in photos and videos of the area that allowed us to write part of its history. We identified economic activities and institutions that are vital to the city, and we observed and recorded our impressions between 2020 and 2023. The importance of the CDC in the life of the city was also proven for the present day, with its proper contextualizations. However, we cannot leave aside the experience as a resident that is not the focus of this research, but produces an interweaving between objectivity and subjectivity, so dear to the theme. It allows us to accept Alain Corbin's challenge of performing a historical immersion in the landscape, or in Walter Benjamin's words, to situate the past as the vanishing point to which our present refers. In this direction, we argue that the landscape only makes sense if it is fully integrated with all its elements, especially the people, who give it meaning. And, we find with Pierre Sansot that he moves away from the pretension of objectivity in his landscape texts. The thesis proposes to maintain a dialogue between distinct eras and expresses the desire that the Ouro Preto landscape be a living legacy for successive and future generations.